2016
DOI: 10.1016/j.ijscr.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer, clinical presentation, diagnosis and treatment: Twenty years of experience in our Breast Unit

Abstract: HighlightsMale breast cancer (MBC) is a rare disease representing less than 1% of all malignancies in men andonly 1% of all incident breast cancers.Management consisted especially of radical mastectomy; followed by adjuvant radiotherapy and hormonal therapy with or without chemotherapy.Future research for better understanding of this disease at national or international level are needed to improve the management and prognosis of male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…According to the literature on the treatment of MBC, modified radical mastectomy is generally preferred to breast conservation surgery (BCS) [8], [9]. Some others reported more radical surgical approach; 71% of patients in Sanguinetti paper treated with more radical treatment such as radical mastectomy (RM) [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature on the treatment of MBC, modified radical mastectomy is generally preferred to breast conservation surgery (BCS) [8], [9]. Some others reported more radical surgical approach; 71% of patients in Sanguinetti paper treated with more radical treatment such as radical mastectomy (RM) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The immunohistochemical study showed an intense and diffuse tumor cells staining for estrogen receptor, a moderate and partial expression for progesterone receptor, which is consistent with previous studies. From the fact that our patient has no factor favouring and shows a Hercep Test of score 3+ (HER2 positive), while the most of the male breast carcinoma BRCA1-related are negative HER2 (4) , we can assume that in this case male breast cancer is secondary to the treatment by the decapeptyl. Radical mastectomy was more commonly used in older case series, likely reflecting both practice patterns (radical and modified radical mastectomies) and later stage at diagnosis of patients in the older series (3) , despite the fact that retrospective studies have shown that the prognosis is the same as for less invasive surgery (15) .…”
Section: Discussionmentioning
confidence: 84%
“…The risk factors are multiple and varied but the genetic factor remains the most important (mutations in BRCA1 and/or BRCA2 genes) (4) . The clinical presentation of the disease differs slightly in men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers observe that disparities exist between the knowledge, treatment and management of female and male breast cancer. They argue that MBC is not properly understood, with some studies indicating that MBC is physically and psychologically different from FBC, and therefore affects men differently to women (Johansson et al 2014;Robinson et al 2008;Ruddy et al 2013;Sanguinetti et al 2016). According to Johansson et al (2014: 527), most of the understanding of MBC has been extrapolated from knowledge of FBC, and even though differences (and some similarities) have been reported, the same information is used to determine management strategies.…”
Section: Disparities Between Female and Male Breast Cancer Messagesmentioning
confidence: 99%